2006
DOI: 10.1002/j.1556-6678.2006.tb00428.x
|View full text |Cite
|
Sign up to set email alerts
|

Intrapersonal and Organizational Factors Associated With Burnout Among School Counselors

Abstract: This study investigated the demographic, intrapersonal, and organizational factors associated with burnout among a population of school counselors in the northeastern United States (n = 78). Three hierarchical regression analyses were completed to determine the amount of variance that each cluster contributed to the 3 subscales on the Maslach Burnout Inventory‐Educators Survey (MBI‐ES; C. M. Maslach, S. E. Jackson, & M. P. Leiter, 1996): Emotional Exhaustion, Depersonalization, and Personal Accomplishment. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
87
1
4

Year Published

2011
2011
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 105 publications
(112 citation statements)
references
References 30 publications
(45 reference statements)
13
87
1
4
Order By: Relevance
“…Preliminary evidence found high burnout was associated with coping by excessively dwelling on one's emotions (emotion‐focused) or avoiding one's emotions (avoidant‐coping) (Ackerley et al., ; Cushway & Tyler, ; Huebner, ; Wilkerson, & Bellini, ), potentially due to reduced opportunities for interpersonal connection and social support (Huebner, ). There were mixed findings on the role of social support, but the majority of studies identified that social support alongside personal therapy, was correlated with high burnout among psychotherapists (Darongkamas et al., ; Kahill, ; Ross et al., ; Stevanovic, & Rupert, ), although it is probable that they were accessing personal therapy as a consequence of (rather than predictor of) burnout (Darongkamas et al., ; Di Benedetto & Swadling, ; Kovach Clark, Murdock, & Koetting, ).…”
Section: Discussionmentioning
confidence: 99%
“…Preliminary evidence found high burnout was associated with coping by excessively dwelling on one's emotions (emotion‐focused) or avoiding one's emotions (avoidant‐coping) (Ackerley et al., ; Cushway & Tyler, ; Huebner, ; Wilkerson, & Bellini, ), potentially due to reduced opportunities for interpersonal connection and social support (Huebner, ). There were mixed findings on the role of social support, but the majority of studies identified that social support alongside personal therapy, was correlated with high burnout among psychotherapists (Darongkamas et al., ; Kahill, ; Ross et al., ; Stevanovic, & Rupert, ), although it is probable that they were accessing personal therapy as a consequence of (rather than predictor of) burnout (Darongkamas et al., ; Di Benedetto & Swadling, ; Kovach Clark, Murdock, & Koetting, ).…”
Section: Discussionmentioning
confidence: 99%
“…As proposed by this theory, job demands-or, job stress-and over-involvement have stronger direct relationships with emotional exhaustion than with depersonalization or personal accomplishment. Various previous studies reported the close relationships among job stress, over-involvement, and emotional exhaustion (Lee & Ashforth, 1996;Maslach, Schaufeli, & Leiter, 2001;Wilkerson & Bellini, 2006). Psychotherapists often face heavy caseloads, leading to job stress.…”
Section: Antecedents Of Burnoutmentioning
confidence: 97%
“…factors, such as organizational and individual factors, that contribute to burnout (Vealey, Udry, Zimmerman, & Soliday, 1992;Wilkerson & Bellini, 2006). Organizational factors are conceptualized as job Stressors such as lack of social support, work overload, role conflict, and role ambiguity (Rupert & Morgan, 2005;Schaufeli & Buunk, 2004).…”
mentioning
confidence: 99%